EFFORTS TO PREVENT THE SPREAD OF COVID-19 IN RECITATION/TPA PARTICIPANTS AT ISLAMIC CENTER MOSQUE, LHOKSEUMAWE CITY - Teuku Ilhami Surya Akbar; Sarah Rahmayani Siregar (LPPM dan PM Universitas Samudra, 2022)
Since Indonesia was declared on alert for Covid-19 in March 2020, the number of patients has shown an increasingly worrying spike, both national and worldwide data. The government is currently imposing a